‘Hey You? Get Off My Cloud’: Evaluation of Cloud Service Models for Business Value within Pharma X - Tassabehji, Rana; Hackney, Ray (Journal of Advances in Management Sciences & Information Systems, 2016)
Recent reports note that managers need to operate at the intersection of business and current innovative technology. Most notably, ‘Strategy is not just informed by technology but powered by it’. The opportunity to evaluate aspects of ‘cloud service models’, as critical new systems, is therefore invaluable. Our research offers a pragmatic view of the characteristics of these technologies and a useful approach for identifying which may be most suitable in relation to the generation of business value. An example is provided of cloud service requirements within a multi-national pharmaceutical company (Pharma X) which is considered as a complex organizational context of significant interest. A highly qualitative methodological approach was adopted from personal interviews with a number of senior managers involved in new technology adoption. The extent of ‘benefits’, ‘risks’, ‘when to use’ and ‘when not to use’ were determined for a variety of common cloud service models to provide a schematic of important issues for evaluation and development. The research is insightful for large private sector multinational organisations which extends an analysis beyond the usual public sector studies. We conclude with lessons learned which demonstrate the most appropriate cloud enabled business models that support senior managers engaged in cloud service processes. Recent reports note that managers need to operate at the intersection of business and current innovative technology. Most notably, ‘Strategy is not just informed by technology but powered by it’. The opportunity to evaluate aspects of ‘cloud service models’, as critical new systems, is therefore invaluable. Our research offers a pragmatic view of the characteristics of these technologies and a useful approach for identifying which may be most suitable in relation to the generation of business value. An example is provided of cloud service requirements within a multi-national pharmaceutical company (Pharma X) which is considered as a complex organizational context of significant interest. A highly qualitative methodological approach was adopted from personal interviews with a number of senior managers involved in new technology adoption. The extent of ‘benefits’, ‘risks’, ‘when to use’ and ‘when not to use’ were determined for a variety of common cloud service models to provide a schematic of important issues for evaluation and development. The research is insightful for large private sector multinational organisations which extends an analysis beyond the usual public sector studies. We conclude with lessons learned which demonstrate the most appropriate cloud enabled business models that support senior managers engaged in cloud service processes. Recent reports note that managers need to operate at the intersection of business and current innovative technology. Most notably, ‘Strategy is not just informed by technology but powered by it’. The opportunity to evaluate aspects of ‘cloud service models’, as critical new systems, is therefore invaluable. Our research offers a pragmatic view of the characteristics of these technologies and a useful approach for identifying which may be most suitable in relation to the generation of business value. An example is provided of cloud service requirements within a multi-national pharmaceutical company (Pharma X) which is considered as a complex organizational context of significant interest. A highly qualitative methodological approach was adopted from personal interviews with a number of senior managers involved in new technology adoption. The extent of ‘benefits’, ‘risks’, ‘when to use’ and ‘when not to use’ were determined for a variety of common cloud service models to provide a schematic of important issues for evaluation and development. The research is insightful for large private sector multinational organisations which extends an analysis beyond the usual public sector studies. We conclude with lessons learned which demonstrate the most appropriate cloud enabled business models that support senior managers engaged in cloud service processes.